Analisis Finansial dan Pemasaran Keranjang Bambu di Desa Sigodang, Kecamatan Panei, Kabupaten Simalungun - Fenny Jepri Yanti Turnip; Agus Purwoko; Tri Martial (Peronema Forestry Science Journal, 2013)
Bamboo was potencial matter as the substitution of wood, especialy in bamboo basket making.  Bamboo basket processing was slowly developed by small industries. This cased aims to determine the financial feasibility and marketing of bamboo basket. To determine the financial feasibility analysis through Cost-Revenue Ratio (R / C), Capital Return Time (Payback Period) and Break Even Point (BEP) analysis. To determine marketing margins distribution used snowball sampling method. The results showed that the financial analysis processing bamboo basket was feasible by R / C was more great than 1 (1.62 and 1.63). There are 3 channels of marketing of bamboo baskets, and the most efficient marketing was channel I. Keywords: bamboo, basket bamboo, financial analysis, marketing channels, marketing margins